1997
DOI: 10.1136/hrt.78.6.581
|View full text |Cite
|
Sign up to set email alerts
|

Florid psychopathology in patients receiving shocks from implanted cardioverter-defibrillators

Abstract: Objectives-To increase awareness of the potential for disabling anxiety and depression in patients receiving shocks from implanted cardioverter-defibrillators (ICDs). Patients and methods-ICDs are implanted in patients at this hospital for control of serious ventricular tachyarrhythmias inadequately controlled by drug treatment, who are unsuitable for map guided antiarrhythmic surgery. All are reviewed regularly at a dedicated ICD clinic and are advised to make contact between visits if they experience shocks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 16 publications
4
42
1
4
Order By: Relevance
“…Teplitz et al 16 and Badger and Morris 13 evaluated ICD support groups and reported that ICD patients and their families shared positive feedback with support group facilitators. The ICD recipients in another study, 9 who did not have a support group available, developed severe anxiety and depression.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Teplitz et al 16 and Badger and Morris 13 evaluated ICD support groups and reported that ICD patients and their families shared positive feedback with support group facilitators. The ICD recipients in another study, 9 who did not have a support group available, developed severe anxiety and depression.…”
Section: Literature Reviewmentioning
confidence: 98%
“…4 A review of the literature on life after ICD implantation reported that patients and their families had difficulty adapting and experienced anger, anxiety, 5 fear, [6][7][8] and depression after experiencing ICD shock. 9 Craney et al 10 found by telephone interview that the majority (74%) of the ICD recipients studied experienced psychological distress as well as poor social and domestic adaptation. Furthermore, Lampert et al 11 found evidence that in patients with an ICD, mental stress may lead to increased incidences of sudden cardiac death through facilitating lethal ventricular arrhythmias, thus making it more compelling to manage this stress.…”
Section: Literature Reviewmentioning
confidence: 98%
“…5) It has been reported that a significant number of ICD patients experience long-term difficulties. 6,7) Some ICD patients have psychological problems, such as anxiety disorders, depression, adjustment disorder and anger. 6,[8][9][10][11][12][13] The reported prevalence of psychological disorders ranged from 15 to 60%.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety disorders, depression and adjustment disorder were the most frequently cited. 6,[8][9][10][11][12] These psychological sequelae have caused impaired quality of life in some ICD patients. Studies on survivors of life-threatening arrhythmias found that the most frequent changes experienced were in lifestyle, increased psychological distress, feelings of dependence and fear of an uncertain future with heart rhythm disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…An important complication of appropriate or inappropriate shocks delivered by implantable defibrillators is that they may evoke serious psychological reactions in up to one third of the patients. 19,20 If the combined use of amiodarone with an ICD is tested prospectively, it is expected that the drug reduces the total mortality and improves the patient's QOL by inhibiting the electrical therapy from the ICDs.…”
Section: Efficacy Of Amiodaronementioning
confidence: 99%